PERBANDINGAN PENAMPILAN REPRODUKSI INDUK SAPI HASIL PERSILANGAN SIMMENTAL x PO (Peranakan Ongole) DI KAWASAN SENTRA PRODUKSI SAPI POTONG KABUPATEN AGAM PROPINSI SUMATERA BARAT - Hidayati Hidayati (Jurnal Peternakan, 2004)
This research was conducted to know the reproductive performances of cows which are offspring of Simmental bull and PO (peranakan OngoIe) crossing. Identification of reproductive perfonnances need to know the abnormality that may cause reproductive retardation. The research was held used survey method with simple random sampling on 113 cows at three. Artificial Insemination Post in Agam, West Sumatera i.e Baso, Biaro and Pakan Kamis. The result showed that reproductive performances of the cows was optimum except on age first service, first service after calving and calving intervaL In addition, the difference of reproductive performances between the first and the second offSpring (Gl and G2) not significant